(untitled) (Journal of Dhaka National Medical College & Hospital, 2015)
The objective of this study was to evaluate the clinical profiles and outcome of primigravida patients in different age group. Materials and method: This study was comparative study which was conducted in the department of Gynaecology and obstetrics, Dhaka National Medical College Hospital, Dhaka. Study period was taken from July 2009 to December 2009. 100 primigravid pregnant women from 36 weeks to 41 weeks in three different groups were included in this study. Group A (20-29 years) with 63 patients, group B (<20 years) with 11 patients & group C (>29 years) with 26 patients. Results: All patients of three groups delivered within or near two years of marriage. In our study, percentage of caesarean section was quite high that is 46% of group A, 45% group B & 96% of group C women. In most cases of group A, LUCS were done due to foetal distress. In group B, due to CPD & in group C, were due to foetal distress and failed trial. Birth asphyxia was more in group B. IUGR was found in only group C about 4%. No significant difference was observed by distribution of pregnant women according to their perinatal morbidity. Conclusion: This study showed teenage and elderly patients were suffered more from different complications. Elderly primigravid patients need comparatively more operative interferences for delivery of their babies . From this study, we should aware to avoid teenage pregnancy and should give special care for elderly primigravid woman during their pregnancy period and labour to achieve healthy mother and healthy foetus. J. Dhaka National Med. Coll. Hos. 2015; 21 (01): 23-27